USE OF GONADOTROPIN-RELEASING HORMONE AGONISTS IN TREATMENT OF RECURRENT PRE-MENSTRUAL ENDOMETRIAL HYPERPLASIA - Yu. E. Dobrokhotova; L. V. Saprykina; N. A. Litvinova; Yu. N. Zadonskay (Акушерство, гинекология и репродукция)
This article presents modern insights into the pathogenesis of endometrium hyperplastic processes, matrix metalloproteinases and their tissue inhibitors, and their role in development of endometrium hyperplasia. A pathogenetic substantiation is given for use of Lucrin Depot, which affects the key molecular mechanisms of development of hyperplastic processes, with the objective of pharmacological correction of this pathology